Exercise Effects on Sleep Physiology - Uchida, Sunao; Shioda, Kohei; Morita, Yuko; Kubota, Chie; Ganeko, Masashi; Takeda, Noriko (Frontiers in Neurology, 2012)
This mini-review focuses on the effects of exercise on sleep. In its early days, sleep research largely focused on central nervous system (CNS) physiology using standardized tabulations of several sleep-specific landmark electroencephalogram (EEG) waveforms. Though coarse, this method has enabled the observation and inspection of numerous uninterrupted sleep phenomena. Thus, research on the effects of exercise on sleep began, in the 1960’s, with a focus primarily on sleep EEG (CNS sleep) changes. Those early studies found only small effects of exercise on sleep. More recent sleep research has explored not only CNS functioning, but somatic physiology as well. As physical exercise mostly affects somatic functions, endocrine and autonomic nervous system (ANS) changes that occur during sleep should be affected by daytime exercise. Since endocrinological, metabolic and autonomic changes can be measured during sleep, it should be possible to assess exercise effects on somatic physiology in addition to CNS sleep quality, building from standard polysomnographic (PSG) techniques. Incorporating measures of somatic physiology in the quantitative assessment of sleep could further our understanding of sleep's function as an auto-regulatory, global phenomenon.